Cognitive-Discursive Study of Migration Discourse (Based on English-Language Media Texts) - N. V. Stepanova (Дискурс, 2021)
Introduction. This article is a fragment of a study on migration discourse. The migration discourse uses a persuasive strategy implemented by means of evaluation information strategy. Evaluation information strategy is carried out mainly through persuasive tactics, which are introduced into the text thanks to the cognitive metaphor. Metaphor allows to compare economic and political concepts with simple and visible images. The construction of conceptual integration schemes makes it possible to track the process of forming a particular image and, consequently, implementing a persuasive strategy in a media text. In modern research, the mechanism of intertextuality can be analyzed in terms of conceptual integration, since intertextual references make a connection with background knowledge.Methodology and sources. The material for the study was articles in English published in American periodicals: https://www.nytimes.com, https://www.washingtonpost.com, as well as on the website https://edition.cnn.com. At the first stage of the study, articles were considered at the text level with the identification of lexical, syntactic and stylistic aspects of the functioning of the discourse. At the second stage (discourse as a discursive practice), examples of intertextuality were investigated, including the depth layer of intertext – cognitive one. The essence of the third stage of work with media texts was the search for interconnection and mutual influence of discourse and social practice. At this stage of the study, the focus of attention was shifted from the media text itself to the socio-political situation in the context of which this text was generated. At each level, an attempt was made to determine which of the means contribute to the realization of the persuasive strategy in the media text and how it is carried out.Results and discussion. The phenomenon of migration is examined in media texts as objectively as possible, both the pros and cons of the migration process are given. The evaluation strategy and related tactics are mainly aimed at describing the actions of politicians. Discrediting tactics directed against Trump are adjacent to Biden’s positive representation tactics and, thus, we-they polarization (we-Biden, they-Trump) through linguistic means, as well as cognitive metaphor is performed. In the articles reviewed, lexemes from the migration and militaristic discourse are often found, and vocabulary describing the events of the coronavirus pandemic period and the accompanying economic crisis are widespread. From the viewpoint of intertextual references, a high percentage of numerals and proper names, which give the impression of the authority of the material, might be of particular interest. The cognitive layer of intertext is widely represented by a conceptual metaphor. Some metaphors discussed in the article participate in the representation of migration and the migration crisis, other metaphors contribute to understanding political and economical processes and phenomena directly or indirectly related to migration. Metaphor-disease, metaphor-natural phenomenon and commoditymaterial metaphor were the most common in the studied body of texts.Conclusion. The migration discourse studied is explicitly related to politics, to issues of power and influence. The persuasive strategy contributes to the construction of images of politicians: Trump is introduced through the mistakes that he made as president of the United States, as well as his inadequate and sometimes cruel actions against migrants, Biden is represented through social problems that he needs to solve performing the role of the president elect. Obviously, the migration issue is a key factor, a test task, which Biden will have to work on immediately after coming to power.